1983
DOI: 10.1099/00222615-16-2-221
|View full text |Cite
|
Sign up to set email alerts
|

The urinary bacterial flora in patients with three types of urinary tract diversion

Abstract: SUMMARY.There is known to be a high risk of malignancy at uretero-colic anastomoses and it has been postulated that bacteria catalyse both the local formation and the activation of carcinogens such as N-nitrosamines. If this theory is correct, then the risk of malignancy should be greatest when the prevalence of mixed urinary tract infection is greatest.Bacterial culture was performed on samples of urine obtained from 56 patients with three forms of urinary tract diversion: ureterosigmoidostomy, isolated ileal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 11 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…SSI in radical surgery with urinary diversion for invasive bladder cancer may depend on two biological and two technical factors. The former involve the patient's underlying condition and extent of the primary disease, and the latter are associated with the surgical technique and urinary diversion 1,13 , 16 . We discuss the present results concerning these factors.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…SSI in radical surgery with urinary diversion for invasive bladder cancer may depend on two biological and two technical factors. The former involve the patient's underlying condition and extent of the primary disease, and the latter are associated with the surgical technique and urinary diversion 1,13 , 16 . We discuss the present results concerning these factors.…”
Section: Discussionmentioning
confidence: 90%
“…The present study showed that most SSI accompanied by diversion can be prevented by AMP on the operative day. Although conduit urine is bacteriuric in most cases, 16 its contribution to SSI is thought to be small. Our results may be useful also in cases requiring urinary diversion for congenital malformations, neurological disorders and incurable inflammatory disease of the urinary tract.…”
Section: Discussionmentioning
confidence: 99%
“…Most patients with urinary diversions become colonized with a multitude of bacteria regardless of the type of diversion. Colonization rates range from 14 to 96%[9–13]. Nonetheless, most of these patients ultimately remain asymptomatic, despite colonization with known uropathogens.…”
Section: Overview Of Risk Factorsmentioning
confidence: 99%
“…Subsequently, Farshi has confirmed the presence of bacterial colonies on the surface of 68% of ureteral stents, although in only 30% of patients was the urine culture was positive [28,29,45]. This author has also shown the correlation between the urinary tract infection and the duration of ureteral stenting [46][47][48][49]. Lifshitz [9] has confirmed the presence of bacterial colonies on the surface of 28-90% of ureteral stents and significant bacteriuria in only 7-34% of patients.…”
Section: Discussionmentioning
confidence: 99%